PENERAPAN METODE EKSPERIMEN DALAM UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS ANAK USIA DINI - Nirwana Nirwana; Reni Maryani (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: the Application of Experimental Methods in an Effort to Improve Science Process Skills in Early childhood. This study aims to improve science process skills of the child through the method of experiment group B Kindergarten. Arya Jaya Sentika Kab. Tangerang. The design of this research uses Classroom Action Research (CAR) conducted collaboratively in two cycles. The subject of this research is a child of class B TK. Arya Jaya Sentika Kab. Tangerang, with a student population of as many as 15 children. Data collection methods conducted in this research is observation,documentation and interviews. The data analysis technique used is descriptive, quantitative and qualitative. The results of this study shows the application of the experimental method can improve the science process skills of students in kindergarten Arya Jaya Sentika Group B. It is based on the data obtained that at the stage of pre action the percentage achieving a 38.6 % is in the criteria began to develop (MB), then increased in cycle I become 55,33% is in the criteria developed according to expectations (BSH), In cycle II the percentage of achievement of science process skills of the child increased to 83% is in the criteria developed very well (BSB).Keywords : experimental method, science process skills.